International Relations in the Digital Age: The Role of Social Media in Public Diplomacy - Faradina, Anggia (Pt. Anagata Sembagi Education, 2025)
In the digital age, social media has become an important tool in public diplomacy, allowing countries to communicate directly with a global audience. This change has significant implications for international relations strategies, facilitating transparency, real-time interaction and rapid information dissemination. This research explores how social media is used by countries to support their public diplomacy objectives and the impact it has on international relations. This research uses a qualitative approach with a case study method. Data was collected through content analysis of social media posts from official government accounts and diplomats from several countries over a period of time. The purpose of this research is to understand the role of social media in public diplomacy and identify strategies used by countries in managing their international image. The research also aims to examine the effectiveness of social media as a public diplomacy tool in influencing international public opinion and building relationships between countries. The results show that social media plays an important role in public diplomacy, allowing countries to effectively convey their messages to a global audience.